2011
DOI: 10.1038/ncomms1503
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming within hours following nuclear transfer into mouse but not human zygotes

Abstract: Fertilized mouse zygotes can reprogram somatic cells to a pluripotent state. Human zygotes might therefore be useful for producing patient-derived pluripotent stem cells. However, logistical, legal and social considerations have limited the availability of human eggs for research. Here we show that a significant number of normal fertilized eggs (zygotes) can be obtained for reprogramming studies. Using these zygotes, we found that when the zygotic genome was replaced with that of a somatic cell, development pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 55 publications
2
45
1
Order By: Relevance
“…27),28) However, human somatic-cell-nucleartransferred cells had arrested at 8 cell stage in development. 29), 30) On the other hand, when a nuclear of somatic cell was transplanted into intact oocyte, these triploid cells succeeded to develop to the blastocyst stage. The established cell lines had pluripotency to differentiate into three germ layers.…”
Section: Cell Fate Conversion By Defined Factorsmentioning
confidence: 99%
“…27),28) However, human somatic-cell-nucleartransferred cells had arrested at 8 cell stage in development. 29), 30) On the other hand, when a nuclear of somatic cell was transplanted into intact oocyte, these triploid cells succeeded to develop to the blastocyst stage. The established cell lines had pluripotency to differentiate into three germ layers.…”
Section: Cell Fate Conversion By Defined Factorsmentioning
confidence: 99%
“…Since isogenic embryonic stem cell lines, known as NT-ESCs, can be derived from nucleartransferred embryos, this technology offers great hope for regenerative medicine. 40 However, due to technical restraints and ethical concerns, it is very hard to obtain patient-specific NT-ESC lines, 41 and until lately, only one research group has successfully derived hESC lines. 42 In 2006, reprogramming of mouse somatic cells into pluripotent stem cells was achieved by ectopically expressing four ESC-enriched transcription factors, namely Oct4, Sox2, Klf4, and C-myc.…”
Section: Mirnas In the Regulation Of Ipscmentioning
confidence: 99%
“…6 Subsequently, they demonstrated that successful genome activation requires that the donor genome goes through a mitotic transition (which facilitates the exchange of somatic for embryonic nuclear factors on the donor nuclear material). 7 How general this phenomenon may be remains to be established. However, using a different reprogramming system, we recently demonstrated that the transcriptional response of donor cells to reprogramming stimuli varies greatly with cell cycle stage.…”
Section: Mitosis and Reprogrammingmentioning
confidence: 99%